Rank among Peers during Game Competition Affects the Tendency to Make Risky Choices in Adolescent Males - Foo, Jerome C.; Nagase, Kohei; Naramura-Ohno, Sawako; Yoshiuchi, Kazuhiro; Yamamoto, Yoshiharu; Morita, Kenji (Frontiers in Psychology, 2017)
It has been shown that adolescents take more risks when they are with peers than when they are alone, presumably because the presence of peers can be a social reward/punishment that can bias decision making. Competition is inherent in peer interactions, and recent work has demonstrated that winning/losing is an intrinsic social reward/punishment. Taken together, it can be hypothesized that competition amongst peers affects adolescents' risky behavior. While there is much evidence that status amongst peers can relate to antisocial/aggressive behavior, it remains unclear whether risky behavior is affected. Moreover, the degree to which ‘temporary status’, such as ranking in a short-term competitive game, affects behavior is uncertain, an important issue because adolescents might be sensitive to situations or factors which potentially destabilize existing hierarchies. In this experiment, these issues were directly explored in the classroom environment using smartphone technology and Wi-Fi setup. Male junior high school students (aged 14-15) performed a roulette game task on smartphones, playing either independently or against five classmates. In the latter case, the students’ current ranks within the group of six were constantly presented on smartphone screens. To dissociate the effects of the students' reactions to ranks from their actual performances, unknown to the students, the ranks presented were actually predetermined so that about half of the students were continuously presented with high ranks whereas the other half were continuously presented with low ranks. We found that the students presented with low ranks made more risky plays than those not presented with ranks or those presented with high ranks. This result suggests that even temporary status significantly affects adolescents' risky behavior, and also demonstrates the usefulness of smartphones in examining and manipulating peer interactions in classroom experiments.